2004
DOI: 10.1111/j.1532-950x.2004.04087.x
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated with Outcome in Dogs Undergoing Extrahepatic Biliary Surgery: 60 Cases (1988–2002)

Abstract: Septic bile peritonitis, preoperative elevated creatinine concentration, and immediate postoperative hypotension in dogs undergoing extrahepatic biliary tract surgery are associated with a poor clinical outcome. Adequate supportive care and monitoring in the perioperative period is critical to improve survival of dogs with extrahepatic biliary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
141
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 25 publications
11
141
1
3
Order By: Relevance
“…Previous studies have shown PTT times, serum concentrations of albumin, globulin, and bilirubin, percentage of band neutrophils, and total lymphocyte counts to also be risk factors for death 10,12,13 In the same studies, reported preoperative risk factors for death in dogs undergoing biliary surgery include age, preanesthetic heart rate, blood urea nitrogen, serum creatinine, GGT, phosphorus, and bilirubin values. 10,12 The risk of death in our dogs increased 0.3 times (30%) for each increment in lactate concentration elevation in the postoperative period. Serum lactate concentrations have been previously investigated in dogs as a significant negative prognostic indicator in disease processes such as gastric dilatation and volvulus, and babesiosis.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have shown PTT times, serum concentrations of albumin, globulin, and bilirubin, percentage of band neutrophils, and total lymphocyte counts to also be risk factors for death 10,12,13 In the same studies, reported preoperative risk factors for death in dogs undergoing biliary surgery include age, preanesthetic heart rate, blood urea nitrogen, serum creatinine, GGT, phosphorus, and bilirubin values. 10,12 The risk of death in our dogs increased 0.3 times (30%) for each increment in lactate concentration elevation in the postoperative period. Serum lactate concentrations have been previously investigated in dogs as a significant negative prognostic indicator in disease processes such as gastric dilatation and volvulus, and babesiosis.…”
Section: Discussionmentioning
confidence: 98%
“…Our finding, however, supports a previous report that found postoperative hypotension to be a significant risk factor for mortality in cases undergoing extrahepatic biliary surgeries. 12 It therefore, warrants careful perioperative monitoring of cases undergoing cholecystectomy, to allow early detection and aggressive management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations